Species of Euglossa Latreille, 1802 (Hymenoptera: Apidae: Euglossina) belonging to the purpurea species group occurring in eastern Brazil, with description of Euglossa monnei sp. n. - Nemésio, André (Zootaxa, 2012)
Species of Euglossa Latreille, 1802 belonging to the Euglossa purpurea Friese, 1899 species group occurring in the Atlantic Forest of eastern Brazil are here revised, illustrated and provided with key for their identification. Seven species of the E. purpurea group were found to occur in eastern Brazil, one of them considered as a new species, Euglossa monnei sp. n. Euglossa avicula is recorded for the first time outside the state of Espírito Santo in the Atlantic Forest and new regional records are presented for other four species. Records of E. avicula outside the Atlantic Forest are dismissed and the identity of some species is discussed.